Erkrankungsrisiko als Krankheit? - Wiese, Lara (Nomos Verlagsgesellschaft mbH & Co. KG, 2024)
The thesis deals with the current and prospective status of persons who are not (yet) ill but have a special risk of disease or a (genetic) disposition in the German statutory health insurance under special consideration of the implications of biomarker-based prediction and early diagnosis. Among other things, it is clarified whether and under what conditions a risk of disease entitles medical treatment, and the consequences of equating risk and illness are examined. Also, a proposal is made, how the law can overcome the outdated dichotomy between health and illness and how the medical needs of the "healthy ill" can be taken into account.